(Un)useful risk disclosure: explanations from the Italian banks. Issue 7 (1st July 2014) - Maffei, Marco; Aria, Massimo; Fiondella, Clelia; Spanò, Rosanna; Zagaria, Claudia
Abstract : Purpose: – The purpose of this paper is to better understand how mandatory risk categories are disclosed and to provide a better understanding of the reasons why risk disclosure looks less useful than it ought to be. Design/methodology/approach: – We analyze how Italian banks provide risk information, by focusing on its characteristics to find out any differences between the notes to the financial statements and the public report, both prepared in compliance with the instructions of the Bank of Italy. We assess the risk-related reporting practices of 66 Italian banks, based on a content analysis of the two mandatory reports, and verify whether bank-specific factors explain any differences. Findings: – Italian banks formally comply with the Bank of Italy's instructions, but there is discretion to choose the characteristics of the information provided. Despite different risk categories to disclose in each report, disclosure is quite uniform, although banks tend to provide denser information in the notes to the financial statements and the difference in the economic signs between the two reports decreases as the level of risk increases. Practical implications: – The significance of this study goes beyond the debate taking place in the academic arena, as it can be largely relevant for preparers, those responsible for setting international and national accounting standards, the Basel Committee on Banking Supervision and the domestic supervisory authorities, particularly concerning the possible introduction of requirements that are more explicit than the existing ones. Originality/value: – The Italian setting is very relevant because unlike other countries, Italy adopts "interventionist enforcements", which are regarded as a critical tool for achieving the minimum disclosure requirements. Moreover, the two sets of disclosure required by the Bank of Italy have never been investigated in a single data set.